Timing of Decompression in Patients with Acute Spinal Cord Injury: A Systematic Review. Issue 1 (April 2016) - Fehlings, Michael; Wilson, Jefferson; Arnold, Paul; Shaffrey, Christopher; Shamji, Mohammed; Mroz, Thomas; Skelly, Andrea; Chapman, Jens R.; Tetreault, Lindsay; Aarabi, Bizhan; Casha, Steve
Introduction: To perform an evidence synthesis of the literature assessing the comparative effectiveness, safety and cost effectiveness of early decompression (≤ 24 hours) versus later decompression (>24 hours) in adults with acute traumatic spinal cord injury. Material and Methods: A systematic search was conducted for literature published through November 6th, 2014. Included studies were critically appraised and GRADE methods were used to determine the overall strength of evidence. Based on clinical expert opinion, an improvement of two or more grades for Frankel or ASIA grades or 5 point improvement in ASIA Motor Score was considered a priori to represent clinically meaningful improvement. Results: Six studies met inclusion criteria. All but one was considered to be a moderately high risk of bias. Single studies in cervical SCI, thoracolumbar SCI, cervical and thoracolumbar SCI, acute central cord injury without instability were identified, and two studies report across SCI levels. Due to the heterogeneity across studies (injury level, measures used, and clinical characteristics), pooling of data was not done. No studies of conservative management met inclusion criteria. No full economic studies or studies of patient preferences or values were identified. Across studies and injury levels, early surgical decompression, defined as surgery ≤ 24 hours of injury, was not consistently associated statistically with clinically important improvement in neurological status. (low to very low strength of evidence) Isolated studies reported statistically significant and clinically important improvement at 6 months for cervical injury and following discharge from inpatient rehabilitation but not at other time points in a population comprised of injury at any level; another study reported a statistically significant 6 point improvement in ASIA Improvement Score only among patients with AIS B, C, or D, but not for those with AIS A. (very low strength of evidence). In one study of acute traumatic cord injury without instability, a clinically and statistically meaningful improvement in total motor scores was seen at six months but not 12 months and there were no statistical differences in ASIA Impairment Scale up to 12 months. (very low strength of evidence) Only one of three studies found a shorter length of hospital stay associated with early surgical decompression. Safety and harms were reported in only three studies; although no statistical differences between early and late decompression were seen, including for mortality, neurologic deterioration, pneumonia or pressure ulcers, studies were underpowered to detect differences particularly for rare outcomes. Conclusion: The overall strength (quality) of evidence across studies was low to very low that early decompression may lead to clinically important improvement in neurologic status in some instances. For studies considering cervical SCI alone and thoracolumbar SCI alone, the overall quality (strength) of evidence was low. For studies involving a combination of cervical, thoracic and lumbar SCI the strength of the same conclusion was very low. Although no statistical or clinically significant differences were noted between early and late groups, firm conclusions regarding the safety of early versus delayed surgical decompression are difficult given small sample sizes and rare events.